ANALYSIS OF THE SUPPLY AND NEEDS OF RED CHILI IN NORTH SUMATRA PROVINCE - Muhammad Fahmi; Akbar Siregar; Ihsan Effendi (Jurnal Ekonomi, 2023)
The purpose of this study was to find out and analyze the availability and demand for red chili in North Sumatra Province. The research area was carried out in North Sumatra Province. The reason for choosing North Sumatra is with the consideration that red chili plants spread throughout the Province of North Sumatra and the research is planned to last for 6 months, this research uses a quantitative approach, in this study the data to be examined is in the form of secondary data in the form of, the price of red chilies in North Sumatra , chili production, rainfall and the price of substitute goods, the data analysis technique used in this study is multiple linear regression analysis, while the results of this study are, in this study partially prices correlate positively and significantly to chili consumption in North Sumatra, p. this is because t count > t table . In this study partially, production correlated not positively and significantly correlated with chili consumption in North Sumatra. In this study partially Rainfall correlated positively and significantly to Chili Consumption in North Sumatra, this is because t count > t table. In this study partially substitutes correlated positively and significantly to chili consumption in North Sumatra, this is because t count > t table. Chili in North Sumatra because f count > f table (28.322>2.57) and sig 0.000 <0.05